2005
DOI: 10.1111/j.1460-9568.2005.04457.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐amyloid inhibition of long‐term potentiation is mediated via tumor necrosis factor

Abstract: A number of recent studies have shown that beta-amyloid (Abeta) inhibits the induction of long-term potentiation (LTP) in the hippocampus. However, little is known about the mechanisms underlying such inhibition of LTP. In the present study, we present evidence that the cytokine tumor necrosis factor (TNF) alpha has a key role in the Abeta inhibition of LTP. The suppression of LTP by Abeta was absent in mutant mice null for TNF receptor type 1 (TNF-R1) and was prevented by the inhibitors of TNFalpha, inflixima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
84
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 37 publications
(91 reference statements)
6
84
0
Order By: Relevance
“…In the CNS, TNF-␣ (through activation of TNFR1) disrupts learning and memory and regulates neuronal death. TNF-␣ has also been shown to participate in A␤-induced inhibition of LTP, a form of synaptic plasticity closely associated with learning and memory, and it is probably dependent on mGluR5 (metabotropic glutamate receptor 5) and p38 MAPK (Wang et al, 2005). Moreover, the activation of programmed cell death seems to rely on the TNF-␣ signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CNS, TNF-␣ (through activation of TNFR1) disrupts learning and memory and regulates neuronal death. TNF-␣ has also been shown to participate in A␤-induced inhibition of LTP, a form of synaptic plasticity closely associated with learning and memory, and it is probably dependent on mGluR5 (metabotropic glutamate receptor 5) and p38 MAPK (Wang et al, 2005). Moreover, the activation of programmed cell death seems to rely on the TNF-␣ signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates the presence of increased levels of TNF-␣ in the brain and plasma of AD patients and an upregulation of TNFR1 have been detected in the AD brain (Fillit et al, 1991;Li et al, 2004). In addition, TNF-␣ has been implicated recently as a critical mediator of long-term potentiation (LTP) reduction by A␤ (Wang et al, 2005). However, the mechanisms through which TNF-␣ promotes its pathological actions in AD are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…This paper presents the first evidence that ryanodine, an inhibitor of ryanodine receptor Ca 2+ -release channels significantly reversed the inhibition of LTP by TNF-α, while having no effect on the induction of LTP at the same concentration. Amyloid-β, which has recently being proposed to inhibit LTP through the activation of the TNF-R1 (p55) receptor (Wang et al, 2005), has previously been shown to reduce NMDA EPSCs (Chen et al, 2002;Snyder et al, 2005) and lead to transient intracellular Ca 2+ rises in cultured hippocampal neurons (Smith et al, 2001). It would be intriguing to speculate if amyloid-β mediated inhibition of LTP could be similarly blocked with ryanodine.…”
Section: Discussionmentioning
confidence: 99%
“…15 Interestingly, the absence of pronounced LTP induction observed in the 3xTg-ADxTNF-RI/RII KO mice differs from previous evidence demonstrating a critical role of TNF-␣ in the A␤-induced inhibition of LTP at hippocampal synapses. Previous work 46 has shown that A␤-induced suppression of hippocampal LTP is absent in mutant mice null for TNF-RI and is prevented by inhibitors of TNF-␣, TNF-␣ peptide antagonists, and TNF-␣ production. These interesting findings were observed in hippocampal slice preparations in the presence of short-term administration of oligomeric A␤ before the onset of LTP induction in mice aged 1 month.…”
Section: Discussionmentioning
confidence: 99%